Workplace Bullying in a Sample of Italian and Spanish Employees and Its Relationship with Job Satisfaction, and Psychological Well-Being - Arenas, Alicia; Giorgi, Gabriele; Montani, Francesco; Mancuso, Serena; Perez, Javier Fiz; Mucci, Nicola; Arcangeli, Giulio (Frontiers in Psychology, 2015)
Purpose – The purpose of this study is to examine the prevalence rate of workplace bullying in a sample of Italian and Spanish employees, and its differential consequences on employees’ job satisfaction and psychological well-being. The effects of workplace bullying on job satisfaction and psychological well-being were explored taking into account a contextualized approach. Design/Methodology/approach – Cross-sectional study was adopted, in which a sample of 1,151 employees in Italy and 705 in Spain completed a questionnaire. We hypothesized that the relationship between exposure to bullying behaviors and psychological well-being is mediated by job satisfaction, and that this simple mediation model is moderated by the country (moderated mediation). Findings – Results suggest that no particular differences exist in bullying prevalence among Spanish and Italian employees. However, we found scientific confirmation of our hypothesized moderated mediation model. Research limitations/implications – Despite the limitations of the sample studied, findings capture contextual differences in the bullying phenomenon, which may have several implications for further research in this domain, as well as for designing interventions to deal with workplace bullying. Originality/value – Although this study explores bullying in different cultural contexts without investigating specific cultural values, it establishes the roots to assess workplace bullying from a contextualized perspective.